A High Performance, Cost-Effective, Open-Source Microscope for Scanning Two-Photon Microscopy that Is Modular and Readily Adaptable - Rosenegger, David G.; Tran, Cam Ha T.; LeDue, Jeffery; Zhou, Ning; Gordon, Grant R. (PLOS ONE, 2014)
Two-photon laser scanning microscopy has revolutionized the ability to delineate cellular and physiological function in acutely isolated tissue and in vivo. However, there exist barriers for many laboratories to acquire two-photon microscopes. Additionally, if owned, typical systems are difficult to modify to rapidly evolving methodologies. A potential solution to these problems is to enable scientists to build their own high-performance and adaptable system by overcoming a resource insufficiency. Here we present a detailed hardware resource and protocol for building an upright, highly modular and adaptable two-photon laser scanning fluorescence microscope that can be used for in vitro or in vivo applications. The microscope is comprised of high-end componentry on a skeleton of off-the-shelf compatible opto-mechanical parts. The dedicated design enabled imaging depths close to 1 mm into mouse brain tissue and a signal-to-noise ratio that exceeded all commercial two-photon systems tested. In addition to a detailed parts list, instructions for assembly, testing and troubleshooting, our plan includes complete three dimensional computer models that greatly reduce the knowledge base required for the non-expert user. This open-source resource lowers barriers in order to equip more laboratories with high-performance two-photon imaging and to help progress our understanding of the cellular and physiological function of living systems.